Recent Advancements in Macrolide Hybrids against Staphylococcus aureus - Ji, Chaofan; Xu, Xiaozhou (Current Topics in Medicinal Chemistry, 2021)
Staphylococcus aureus (S. aureus), recognized as one of the deadliest pathogens responsible for nosocomial and community acquired infections, is highly contagious and associated with significant morbidity and mortality. The increasing emergency and rapid spread of various forms of drug-resistant S. aureus have already posed a heavy burden on the world health system, but newfangled antibiotics are right now being created at a much slower pace than our developing requirement. Macrolides could inhibit protein synthesis by targeting the bacterial ribosome and are a class of basic and widely used antibacterial agents in clinical practice to control infections caused by various bacteria, including S. aureus. However, the emergence of bacterial resistance to macrolide antibiotics, particularly in Gram-positive bacteria such as macrolide-resistant S. aureus, has already become one of the significant obstacles for effective chemotherapy. Therefore, there is a critical need for the development of novel macrolide candidates. This review provides an overview of macrolide hybrids with potential activity against S. aureus, including drug-resistant forms developed in the recent decade, with special emphasis on the structure-activity relationships and mechanism of actions.
Keywords: Antibacterial